Efficacy of probiotics in irritable bowel syndrome: A randomized, double blind placebo-controlled study (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Gut flora have important trophic effects on intestinal epithelia and on immune structure and fonction.They also protect colonized host against invasion by alien microbes.Recent research suggests that an imbalance of the intestinal microbiota and a dysfunctional intestinal barrier might trigger irritable bowel syndrome (lBS). As probiotics have been reported to restore the intestinal microbiota and the gut barrier, the therapeutic potential of probiotics within IBS became of strong interest. Objectives: To assess the efficacy of probiotics in lBS. Methods: Patients of 15 to 60 years old and both sexes were included f om the out patient department (OPD) of gastroenterology, Bangabandhu Sheikh Mujib Medical University (BSMMU). A validated lBS-QOL instmment consisted of 34 questions used to assess improvement of quality of Iife before and after treatment. A total of 65 diarrhoea predominant LBS patients were randomised to receive either probiotics(n-33) or placebo(n-32) twice daily frir 6 weeks.Results: At the end of 6 weeks therapy, improvement in various symptoms(abclominal pain, stool frequency, consistency and 11atulence) in probiotics group was statistically significant. Mean QOL score before treatment was 103 in probiotics group and I 06 in placebo group. After 6 weeks of treatment mean QOL score was 82 in probiotics group and I 02.58 in placebo group. No side effects of the therapeutic agents were observed in any patient during the trial. Conclusions: Probiotics effectively alleviates global IBS and improves TBS symptoms simultaneously with an improvement of quality of life.